Iron Export through the Transporter Ferroportin 1 Is Modulated by the Iron Chaperone PCBP2 - Yanatori, Izumi (J Biol Chem, 2016)
Ferroportin 1 (FPN1) is an iron export protein found in mammals. FPN1 is important for the export of iron across the basolateral membrane of absorptive enterocytes and across the plasma membrane of macrophages. The expression of FPN1 is regulated by hepcidin, which binds to FPN1 and then induces its degradation. Previously, we demonstrated that divalent metal transporter 1 (DMT1) interacts with the intracellular iron chaperone protein poly(rC)-binding protein 2 (PCBP2). Subsequently, PCBP2 receives iron from DMT1 and then disengages from the transporter. In this study, we investigated the function of PCBP2 in iron export. Mammalian genomes encode four PCBPs (i.e. PCBP1–4). Here, for the first time, we demonstrated using both yeast and mammalian cells that PCBP2, but not PCBP1, PCBP3, or PCBP4, binds with FPN1. Importantly, iron-loaded, but not iron-depleted, PCBP2 interacts with FPN1. The PCBP2-binding domain of FPN1 was identified in its C-terminal cytoplasmic region. The silencing of PCBP2 expression suppressed FPN1-dependent iron export from cells. These results suggest that FPN1 exports iron received from the iron chaperone PCBP2. Therefore, it was found that PCBP2 modulates cellular iron export, which is an important physiological process.